Análise da Utilização de Produtos Ambientalmente Amigáveis como Inibidores de Corrosão em Ambientes Contendo CO2 - Monteiro, Mariana Vieira Casanova (2018)
Pipeline internal corrosion is one of the serious problems that occur in the oil and gas industry. The CO2 presence in produced fluids can cause corrosion of the material. The use of inhibitors is one of the most commonly used methods for corrosion control. However, most substances are non-biodegradable synthetic chemicals and can be hazardous to living beings and the environment. The present work studied the influence of three environmentally-friendly components on the API 5L X65 steel corrosion inhibition in CO2-saturated 3.5 wt.% NaCl brine. From an experimental design, eight blends were tested. In addition, the effects of shear stress, test duration, pH value and the iron carbonate film previously formed on the metal surface were also evaluated. The results indicated which blends are stable and capable to provide corrosion protection in the 72 hours tested, as well as the component that most influences the inhibition. The rotating cylindrical electrode introduced the shear stress effect in the system and decreased inhibition efficiencies; and the iron carbonate film interfered in the inhibitor adsorption on the sample surface. The blend containing the highest concentration of the three components presented the most satisfactory inhibition efficiencies at different conditions of pH value, test duration and flow regime.